Molecular Structure Studies on Calicene and Calicene-Like Containing Heavier Atoms Using DFT Calculations - Vessally, E. (Asian Journal of Chemistry, 2010)
DFT calculations are carried out on molecular structure of calicene and calicene-like containing heavier atoms; 5-cycloprop-2-enylidene-cyclopenta-1,3-diene (CC), 1-cycloprop-2-enylidene-1H-silole (CSi), 1-cycloprop-2- enylidene-1H-germole (CGe), 1-cycloprop-2-enylidene-1H-stannole (CSn), 1-cyclopenta-2,4-dienylidene-1H-silirene (SiC), 1-siliren-1-ylidene-1H-silole (SiSi), 1-germol-1- ylidene-1H-silirene (SiGe), 1-cyclopenta-2,4-dienylidene-1H-germirene (GeC), 1-germiren-1-ylidene-1H-silole (GeSi), 1-germiren-1-ylidene-1H-germole (GeGe), 1-cyclopenta-2,4- dienylidene-1H-stannirene (SnC), 1-stanniren-1-ylidene-1H-silole (SnSi), at B3LYP/6-311++G** level of theory. The stability of conformations are discussed and compared.